The Miserable Loss from Yemeni Conflict: Can International Law Provide Reparation for Mental Injury? - Komang Ayu Nuriasih; I Made Budi Arsika (Hasanuddin Law Review, 2020)
As the home of the world’s worst humanitarian crisis, Yemen can be an example to reveal how horrifying the mental health issues in conflicting areas can be. Since 2014, the ongoing conflict in Yemen has been resulting not merely in physical losses and injuries, but also mental catastrophe as its inevitable consequence. This article is a legal research that aims to analyze how mental injuries or psychological damages are being acknowledged as a real impact of armed conflict, to further be considered as a precondition for the reparation at the end of the conflict. The article suggests that the acknowledgment of the mental impacts of armed conflict needs to be taken into concern and consideration, especially from the perspective of  hard laws related to the IHL. Besides, the approach of soft law can be applied in attribution with the ongoing conflict in Yemen.